Smart Learning Platform for Management Executive: A Systematic Literature Review - Umar Al Faruqi (APIC, 2019)
Development of digital transformation towards the information age have made significant change in various sectors and industries, including education. This transformation also needs to consider social problem solving with human centered design approach. One of the learning methods enabled by the technology development of this transformation is smart learning, that aims to improve the quality of learning utilizing intelligent technology in accordance with the learning context. This paper explains systematic literature review conducted as initial study in the research of smart learning for executives. The journals used in this review are various international journals obtained from some reputable journal databases. After going through the filtering process using several inclusion and exclusion criteria, 15 journals were analyzed based on the research questions. From the review, it can be concluded that smart learning can improve the learning process in terms of motivation, engagement, and learning performance. Various information technology is used to enhance the efficiency and effectiveness of smart learning, which provides the learning needs for executive education.